Host-Microbiome Cross-talk in Oral Mucositis. (July 2016) - Vasconcelos, R.M.; Sanfilippo, N.; Paster, B.J.; Kerr, A.R.; Li, Y.; Ramalho, L.; Queiroz, E.L.; Smith, B.; Sonis, S.T.; Corby, P.M.
Oral mucositis (OM) is among the most common, painful, and debilitating toxicities of cancer regimen–related treatment, resulting in the formation of ulcers, which are susceptible to increased colonization of microorganisms. Novel discoveries in OM have focused on understanding the host-microbial interactions, because current pathways have shown that major virulence factors from microorganisms have the potential to contribute to the development of OM and may even prolong the existence of already established ulcerations, affecting tissue healing. Additional comprehensive and disciplined clinical investigation is needed to carefully characterize the relationship between the clinical trajectory of OM, the local levels of inflammatory changes (both clinical and molecular), and the ebb and flow of the oral microbiota. Answering such questions will increase our knowledge of the mechanisms engaged by the oral immune system in response to mucositis, facilitating their translation into novel therapeutic approaches. In doing so, directed clinical strategies can be developed that specifically target those times and tissues that are most susceptible to intervention.